2001
DOI: 10.1023/a:1012399114305
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this study, the effect of hyperthermia on immune response and bacterial translocation from the gut in jaundiced rats was assessed. In hyperthermic (HP; N = 8) and normothermic (NP; N = 8) preconditioning groups, rats were preconditioned by hyperthermia for 15 min at 42 degrees C or 38 degrees C, respectively. After 8 hr, the common bile duct (CBD) of each animal was ligated. In thermal (TT; N = 8) and normothermic treatment groups (NT; N = 8) the CBD of the animals was ligated, and after seven days rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…Notably, hyperthermia preconditioning has been demonstrated to be an effective method to protect against OJ-induced liver injury in rats (9). The results from this study were in accordance with previous studies, which demonstrated that hyperthermic preconditioning enhances the immune response of rats with OJ (10,11). …”
Section: Introductionsupporting
confidence: 93%
“…Notably, hyperthermia preconditioning has been demonstrated to be an effective method to protect against OJ-induced liver injury in rats (9). The results from this study were in accordance with previous studies, which demonstrated that hyperthermic preconditioning enhances the immune response of rats with OJ (10,11). …”
Section: Introductionsupporting
confidence: 93%
“…This improvement suggests an enhancement in the body's immune function to some extent. Additionally, there is evidence demonstrating that exposing lymphokine-activated killer cells to temperatures above 45 degrees Celsius significantly enhances their tumor-killing activity 20 . Furthermore, this temperature exposure also enhances the immune effects of macrophages, lymphocytes, and other cells 21 .…”
Section: Discussionmentioning
confidence: 99%